2016
DOI: 10.1111/trf.13880
|View full text |Cite
|
Sign up to set email alerts
|

Blood component transfusion and wastage rates in the setting of massive transfusion in three regional trauma centers

Abstract: A large portion of blood products issued during MTPs are not transfused. Some are wasted due to stringent storage requirements and/or limited shelf lives. The optimum ratio of transfused to returned products in these patients is likely to be determined more by clinical need than by transfusion service policy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
30
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 11 publications
2
30
1
1
Order By: Relevance
“…This study demonstrated high utilization and generally low wastage rates for blood products issued during obstetric hemorrhage. In particular, the transfusion rate of PLTs and cryoprecipitate was higher than that observed in a study of MTP recipients at three large American hospitals …”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…This study demonstrated high utilization and generally low wastage rates for blood products issued during obstetric hemorrhage. In particular, the transfusion rate of PLTs and cryoprecipitate was higher than that observed in a study of MTP recipients at three large American hospitals …”
Section: Discussioncontrasting
confidence: 65%
“…However, compared to primarily trauma patients on whom an MTP was ordered in an earlier study at three hospitals, a generally higher rate of receiving at least one blood product in obstetric hemorrhage was observed. This was especially true for PLTs and cryoprecipitate, where the receipt rates in obstetric hemorrhage patients were 74 and 91%, respectively, compared to 16% to 49% and 11% to 26%, respectively, for the MTP patients . Perhaps these higher rates of transfusion of at least 1 unit relates to the specific nature of this type of hemorrhage, that is, perhaps the need for blood product support in obstetric hemorrhage is more predictable when it occurs compared to other patients on whom an MTP has been ordered.…”
Section: Discussionmentioning
confidence: 62%
“…One possible disadvantage of the generic MTP approach, however, may be an inefficient use of resources. Nontrauma MTP activations have been associated with fewer transfused components, with some studies showing increased blood component wastage . To address this, some centers have successfully implemented multiple MTPs (such as a trauma specific MTP and a nontrauma MTP) to optimize inventory management .…”
Section: Discussionmentioning
confidence: 99%
“…Nontrauma MTP activations have been associated with fewer transfused components, with some studies showing increased blood component wastage. 17,18 To address this, some centers have successfully implemented multiple MTPs (such as a trauma specific MTP and a nontrauma MTP) to optimize inventory management. 17 This is the largest study to date describing the clinical indications for MTP activations.…”
Section: Discussionmentioning
confidence: 99%
“…Chay and coworkers tell of the implementation of a national 1:1:1 protocol across seven major hospitals in Singapore that improved time of blood products to the patient, but achieved actual ratios of 1:0.8:0.8. Dunbar and colleagues reviewed the wastage rates for blood components at three Level I trauma centers and found them to be high with misstorage of issued products. Planned thawing and issuing of cryoprecipitate was particularly wasteful with 7% to 33% wastage across the sites.…”
Section: Discussionmentioning
confidence: 99%